INNOVATION, SERVICE QUALITY, CUSTOMER TRUST DAN CUSTOMER SATISFACTION PADA CUSTOMER TOKO INDOMARET HO PIK JAKARTA - Janet, Derin El Safira; Sirait, Tongam (ITB AAS Indonesia Surakarta, 2024)
The purpose of this study is to determine the influence of innovation, service quality, customer satisfaction either directly or indirectly through the mediating effect of customer trust. This study discusses about customer satisfaction on application klik indomaret customer in HO PIK Jakarta. The object of the research is klik indomaret users in HO PIK Jakarta, with 115 respondents participated as the samples. This study uses quantitative method with purposive random sampling as sampling method. The analysis techniques used are descriptive analysis and Structural Equation Modeling (SEM) using SmartPLS v.3.0. The results of this research indicated that innovation disclosure has a positive influence on customer trust, service quality has not influence on customer trust, innovation has no influence on customer satisfaction, service quality has a positive influence on customer satisfaction, customer trust has a positive influence on customer satisfaction